2019
DOI: 10.2147/ott.s183435
|View full text |Cite
|
Sign up to set email alerts
|

<p>miR-129-5p inhibits prostate cancer proliferation via targeting ETV1</p>

Abstract: Background Prostate cancer is one of the most commonly diagnosed diseases in males. Methods RT-qPCR was used to detect miR-129-5p expression in tumor tissues and adjacent normal tissues from patients with prostate cancer. The cell proliferation assay and colony forming assay were used to study the role of miR-129-5p in mediating prostate cancer cell growth. Bioinformatic analysis and dual luciferase assay were performed to predict and confirm ETV1 as a target gene of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 44 publications
3
30
0
Order By: Relevance
“…Meanwhile, the expression of miR‐129‐5p in the growth plate was also verified by in situ hybridization. Several studies 26,27 have indicated that miR‐129‐5p can inhibit the proliferation of prostate cancer cells, is expressed by osteoblasts in rheumatoid arthritis, 28 and can directly inhibit IL‐17 expression. Nevertheless, the expression of miR‐129‐5p in chondrocytes and growth plates has not yet been reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the expression of miR‐129‐5p in the growth plate was also verified by in situ hybridization. Several studies 26,27 have indicated that miR‐129‐5p can inhibit the proliferation of prostate cancer cells, is expressed by osteoblasts in rheumatoid arthritis, 28 and can directly inhibit IL‐17 expression. Nevertheless, the expression of miR‐129‐5p in chondrocytes and growth plates has not yet been reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…Dual functions for miR-129, as a tumor suppressor and oncogene, have been confirmed in various types of carcinomas. miR-129-5p has been reported to be downregulated in neuroendocrine tumors, prostate cancer, lung cancer and gastric cancer and functions as a tumorsuppressor role in these carcinomas [22][23][24]. Epigenetic regulation of miR-129-2 was demonstrated in glioma and lung cancer [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR-182 16 , miR-30a 17 and miR-200c-3p 18 act as tumor suppressors to inhibit the progression of ccRCC by respectively targeting IGF1R, ADAM9 and SLC6A1, while miR-654 19 and miR-543 20 facilitate ccRCC cell proliferation and metastasis by targeting GK5 and Krüppel-like factor 6 (KLF-6), respectively. Generally speaking, miR-129-5p is considered to be a tumor suppressor and is down-regulated in prostate cancer (PC) 21 , bladder cancer (BC) 22 , etc. Wu Z et al pointed out that the long non-coding RNA SNHG12 acts as a competing endogenous RNA to regulate MDM4 expression by competing with miR-129-5p in ccRCC 12 .…”
Section: Discussionmentioning
confidence: 99%